Biomarker responses in wild brown trout from a headwater stream and their causal link to water pollution assessed through chemical analysis and in vitro reporter gene bioassays - Koubová, Anna; Toušová, Zuzana; Šauer, Pavel; de Sales-Ribeiro, Carolina; Vrana, Branislav; Smutná, Marie; Kocour Kroupová, Hana; Grabicová, Kateřina; Schmidt-Posthaus, Heike; Randák, Tomáš; Grabic, Roman; Hilscherová, Klára; et al. (Journal of hazardous materials, 2025)
Improving our understanding of how environmental pollution affects aquatic life requires a holistic approach. This study provides new insights into the intrinsic biological defence of brown trout (Salmo trutta m. fario L.) against chemical pollution in a stream with a low-dilution factor, a common scenario in headwaters globally. Fish restocked downstream of a sewage treatment plant (STP) were compared with a control group upstream of STP. Trout tissues were sampled after 6, 14, and 24 weeks and subjected to biochemical and histological analyses. Passive samplers were deployed at both stream stretches to reflect concentrations of freely dissolved organic micropollutants and their bioactivity effects using in vitro reporter gene bioassays. Chemical analysis downstream revealed elevated concentrations of micropollutants compared to upstream. In vitro bioassays detected increased androgenicity, estrogenicity, and transthyretin-binding inhibition. Antioxidant and biotransformation enzyme activities in fish indicated gradual acclimation to pollution despite minor histopathological changes. Elevated vitellogenin and 17β-estradiol in males suggested pollution-induced endocrine disruption. Although the results obtained from water chemical profiling and bioassays have a causal relationship to fish health, trout's molecular defence system allowed gradual acclimation to pollution, mitigating broader ecological impacts. The study advanced the knowledge of how fish cope with wastewater-borne micropollutants in aquatic environments.
Keywords: Histology; Antioxidant enzymes; biotest; Trout; estradiol; Endocrine Disruptors; Environmental Monitoring; Cytochrome P450; Female; řeky; Biomarkers; zvířata; pstruh; reportérové geny; Rivers; monitorování životního prostředí; endokrinní disruptory; biologické markery; ženské pohlaví; Estradiol; Male; Biological Assay; Genes, Reporter; Passive sampler; Water Pollutants, Chemical; Vitellogenins; vitelogeniny; Micropollutant; Animals; mužské pohlaví; chemické látky znečišťující vodu